2009
DOI: 10.1038/nature08596
|View full text |Cite
|
Sign up to set email alerts
|

Central control of fever and female body temperature by RANKL/RANK

Abstract: Receptor-activator of NF-kappaB ligand (TNFSF11, also known as RANKL, OPGL, TRANCE and ODF) and its tumour necrosis factor (TNF)-family receptor RANK are essential regulators of bone remodelling, lymph node organogenesis and formation of a lactating mammary gland. RANKL and RANK are also expressed in the central nervous system. However, the functional relevance of RANKL/RANK in the brain was entirely unknown. Here we report that RANKL and RANK have an essential role in the brain. In both mice and rats, central… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
167
2
7

Year Published

2011
2011
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(180 citation statements)
references
References 21 publications
4
167
2
7
Order By: Relevance
“…Initial in vitro studies implicated RANKL in regulating osteoclast formation and function (33, 73), immune cell survival and activation such as dendritic cell (DC) survival and activation (78-80), and T-cell activation (81, 82). However, RANKL and RANK knockout models further revealed that the RANKL/RANK/OPG system also plays a role in lymph node organogenesis (81, 83, 84), B-cell differentiation (81, 83), development of medullary thymic epithelial cells (85,86), mammary gland development (87), and thermoregulation in females, as well as fever response in inflammation (88).…”
Section: Rankl Rank and Osteoprotegrin (Opg)mentioning
confidence: 99%
“…Initial in vitro studies implicated RANKL in regulating osteoclast formation and function (33, 73), immune cell survival and activation such as dendritic cell (DC) survival and activation (78-80), and T-cell activation (81, 82). However, RANKL and RANK knockout models further revealed that the RANKL/RANK/OPG system also plays a role in lymph node organogenesis (81, 83, 84), B-cell differentiation (81, 83), development of medullary thymic epithelial cells (85,86), mammary gland development (87), and thermoregulation in females, as well as fever response in inflammation (88).…”
Section: Rankl Rank and Osteoprotegrin (Opg)mentioning
confidence: 99%
“…One recent report showed that astrocytes are involved in fever induced by RANKL and cytokines. Hanada et al (2009) showed that inactivation of the RANK receptor in neuronal progenitor cells as well as inactivation of this receptor only in astrocytes abolished fever in response to RANKL, IL1b, and TNF-a (Hanada et al 2009), indicating that astrocytes are major contributors to inflammationinduced fever. Thus, MC4R activation in astrocytes could help reduce fever by inhibiting release of mediators such as cytokines and PGs.…”
Section: Mc4r and Inflammationmentioning
confidence: 99%
“…Recently, the RANKL/RANK system was described as another important mediator of fever caused by LPS or cytokines in mouse brain (Hanada et al 2009). As levels of a-MSH increase in the brain during fever (Bell & Lipton 1987) and circulating levels of a-MSH increase in response to endotoxin administration in humans (Catania et al 1995), a physiological role for melanocortins in fever has been suggested.…”
Section: Mc4r and Inflammationmentioning
confidence: 99%
“…The normal osteoclast activation results in physiological bone resorption in bone remodeling, whereas overactivated osteoclasts result in various bone diseases such as osteoporosis and rheumatoid arthritis (8,9). Besides the best-known critical roles in bone remodeling, RANKL also plays multiple roles in immune system (10), mammary gland development (11), cancer bone metastasis (12), hormone-derived breast cancer development (13), and thermal regulation (14). Therefore, the RANKL-RANK-OPG molecular triad is an attractive target to develop rational therapy for many osteopenic conditions and prevent bone destruction in osteoporosis and arthritis (15).…”
mentioning
confidence: 99%